2021
DOI: 10.3390/ijerph18094422
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Multimorbidity and Polypharmacy Patterns in Young and Adult Population over a 4-Year Period: A 2011–2015 Comparison Using Real-World Data

Abstract: The pressing problem of multimorbidity and polypharmacy is aggravated by the lack of specific care models for this population. We aimed to investigate the evolution of multimorbidity and polypharmacy patterns in a given population over a 4-year period (2011–2015). A cross-sectional, observational study among the EpiChron Cohort, including anonymized demographic, clinical and drug dispensation information of all users of the public health system ≥65 years in Aragon (Spain), was performed. An exploratory factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Earlier studies focusing on chronic conditions identified from electronic health records evidenced the existence of systematic associations between chronic diseases, whereby chronic diseases, often from dissimilar disease categories, coappeared within a multimorbidity pattern or cluster [24][25][26]. Importantly, though, these studies showed that the complexity of multimorbidity patterns in terms of diseases and associated drug use increased with age, which holds true for both genders.…”
Section: Discussionmentioning
confidence: 98%
“…Earlier studies focusing on chronic conditions identified from electronic health records evidenced the existence of systematic associations between chronic diseases, whereby chronic diseases, often from dissimilar disease categories, coappeared within a multimorbidity pattern or cluster [24][25][26]. Importantly, though, these studies showed that the complexity of multimorbidity patterns in terms of diseases and associated drug use increased with age, which holds true for both genders.…”
Section: Discussionmentioning
confidence: 98%
“…It is logical to think that some combinations of diseases may have a higher impact on health than others and that pharmacological management plays a vital role in clinical outcomes. The high mean number of diseases and drugs in older adults may involve disease–disease, drug–drug, and drug–disease interactions, as well as prescribing cascades [ 68 , 69 ], increasing the risk of potentially inappropriate medication and its clinical consequences [ 70 , 71 , 72 ]. An interesting finding, for example, was the high use of drugs with anticholinergic activity in clusters with dementia, especially in octogenarians and nonagenarians.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is possible that the characteristics of patients prescribed hypnotics or anxiolytics changed in the periods. By incorporating disease information, we could better understand the relationship between the trend of drug prescriptions and diseases [ 31 ]. However, one strength of this study is that we revealed the prescription trends, particularly in elderly patients, and trends observed in recent years.…”
Section: Discussionmentioning
confidence: 99%